The communicator for development and social change. Notes for the construction of its profile - Huarcaya, Gloria (2022)
It is a common thinking that communicator's professional landscape ends in journalism and other derives, as corporate communication, marketing and advertising. Even academia has proven little interest in communicators for development and social change, a practitioner that play an important role in development processes in order to promote the participation of stakeholders. The following paper offers a review on this practitioner's profile from the standpoint of his professional exercise, one that links and includes knowledge, skills and communication attitudes, anthropology as well as education.